Enhanced performance of thin-film nanocomposite forward osmosis membranes via organic-phase incorporation of functionalized multiwalled carbon nanotubes - H. E. Almansouri; M. N. Abu Seman; C. K. M. F. Che Ku Yahya; A. W. Mohammad; A. Al Hinai (International Journal of Environmental Science and Technology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Uncovering hidden threats: prevalence, antibiotic resistance and virulence gene profiles of Escherichia coli strains isolated from Testudines and their aquatic habitats - Lungile N. Mlangeni; Tsepo Ramatla; Cormac Price; Oriel Thekisoe; Che Weldon (Molecular Biology Reports, 2025)
Background The gut microbiota of Testudines is fundamental to their digestion and overall health, yet remains a poorly investigated area in their biology, particularly in wild freshwater turtle (terrapins) and tortoise populations within South Africa. This study investigated the occurrence, diversity, virulence genes and antibiotic resistance of Escherichia coli isolated from Testudine gut microbiota and sediments at Timbavati Private Nature Reserve, South Africa. Methods and results Cloacal swab samples were collected from 36 wild Testudines and 20 sediment samples from temporary and permanent water bodies. Presumed E. coli isolates were confirmed by polymerase chain reaction (PCR) targeting the β -D glucuronidase ( uidA ) gene and further validated through 16 S rRNA gene sequencing. Phenotypic antibiotic resistance was evaluated with the Kirby-Bauer method, whilst resistance and virulence genes were identified using PCR assays. E. coli was detected in 54 (62%) of 87 isolates (23 Testudines and 31 sediments), confirmed by uidA PCR assay. Detected virulence genes included eaeA (42%), virF (22%), stx1 (16%), and stx2 (3%), and isolates exhibited resistance to erythromycin (53%), cephalothin (48%), and spectinomycin (40%). Resistance genes such as mcr-4 (70%), bla SHV (46%), bla TEM (64%), mcr-1 (42%), qnrA (16%), mcr-2 (22%), qnrD (11%), and tetW (2%) were also detected. Conclusions This study demonstrates that wild Testudines harbour E. coli in their gut and that it also occurs in their surrounding environment, with notable antibiotic resistance and virulence potential. The findings underscore the complexity of host-microbial interactions and the influence of environmental and host factors on microbial diversity, informing potential conservation and health management strategies for these reptilian species.

Ultrafiltration process for white spot syndrome virus (WSSV) mitigation strategy in indoor shrimp farming system - Diyana Kamarudin; Nora’aini Ali; Norhafiza I. Yatim; Sandra C. Zainathan; Siti N. K. Addis; Che A. C. Johan; Nor A. Kasan (Aquaculture International, 2025)

A balanced approach to the potential of octopus aquaculture - Ian G. Gleadall; Roger Villanueva; Gregory J. Barord; Zoe Doubleday; Felipe Aguado-Giménez; Nobuhiko Akiyama; Eduardo Almansa; Cheryl L. Ames; Alexander Arkhipkin; Otilio Avendaño; Chris Barrett; Giambattista Bello; et al. (Marine Policy, 2025)

Twelve strategies for realizing the promise of ecopracticology - Steven J. Cooke; Marco Carlotti; Kgosietsile Velempini; Nathan Heavers; Zhifang Wang; Zoe Moula; Qinghe Hou; Andrew Howarth; Meagan Harper; Andrew N. Kadykalo; Yasuhisa Kondo; Yue Che; et al. (Socio-Ecological Practice Research, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Investigating the influence of the composition of the modified lignin-epoxy coating on hydrophobicity, using Box–Behnken design optimization model - N. E. Chowdhury; P. S. M. Bt Megat Yusoff; M. B Mustapha; N. F. Bt Che Lah (International Journal of Environmental Science and Technology, 2024)

Columnar aerosol types and compositions over peninsular Southeast Asia based on long-term AERONET data - Sheng-Hsiang Wang; Hsiang-Yu Huang; Che-Hsuan Lin; Shantanu Kumar Pani; Neng-Huei Lin; Chung-Te Lee; Serm Janjai; Brent N. Holben; Somporn Chantara (Air Quality, Atmosphere & Health, 2024)
Aerosol chemical components such as black carbon (BC) and brown carbon (BrC) regulate aerosol optical properties, which in turn drive the atmospheric radiative forcing estimations due to aerosols. In this study, we used the long-term measurements from AERONET (Aerosol Robotic Network) to better understand the aerosol types and composition with respect to their seasonal and spatial variabilities in peninsular Southeast Asia (PSEA, here defined as Vietnam, Cambodia, Thailand, Laos, and Myanmar). Two methods (i.e., aerosol type cluster and aerosol component retrieval) were applied to determine the aerosol type and chemical composition during the biomass-burning (BB) season. AERONET sites in northern PSEA showed a higher AOD (aerosol optical depth) compared to that of southern PSEA. Differences in land use pattern, geographic location, and weather regime caused much of the aerosol variability over PSEA. Lower single-scattering albedo (SSA) and higher fine-mode fraction (FMF) values were observed in February and March, suggesting the predominance of BB type aerosols with finer and stronger absorbing particles during the dry season. However, we also found that the peak BB month (i.e., March) in northern PSEA may not coincide with the lowest SSA once dust particles have mixed with the other aerosols. Furthermore, we investigated two severe BB events in March of 2014 and 2015, revealing a significant BrC fraction during BB event days. On high AOD days, although the BC fraction was high, the BrC fraction remained low due to lack of aerosol aging. This study highlights the dominance of carbonaceous aerosols in the PSEA atmosphere during the BB season, while also revealing that transported dust particles and BrC aerosol aging may introduce uncertainties into the aerosol radiative forcing calculation.

The call of the emperor penguin: Legal responses to species threatened by climate change - Stephanie Jenouvrier; Judy Che‐Castaldo; Shaye Wolf; Marika Holland; Sara Labrousse; Michelle LaRue; Barbara Wienecke; Peter Fretwell; Christophe Barbraud; Noah Greenwald; Julienne Stroeve; Philip N. Trathan (Global Change Biology, 2021)
Species extinction risk is accelerating due to anthropogenic climate change, making it urgent to protect vulnerable species through legal frameworks in order to facilitate conservation actions that help mitigate risk. Here, we discuss fundamental concepts for assessing climate change risks to species using the example of the emperor penguin ( Aptenodytes forsteri ), currently being considered for protection under the US Endangered Species Act (ESA). This species forms colonies on Antarctic sea ice, which is projected to significantly decline due to ongoing greenhouse gas (GHG) emissions. We project the dynamics of all known emperor penguin colonies under different GHG emission scenarios using a climate‐dependent meta‐population model including the effects of extreme climate events based on the observational satellite record of colonies. Assessments for listing species under the ESA require information about how species resiliency, redundancy and representation (3Rs) will be affected by threats within the foreseeable future. Our results show that if sea ice declines at the rate projected by climate models under current energy system trends and policies, the 3Rs would be dramatically reduced and almost all colonies would become quasi‐extinct by 2100. We conclude that the species should be listed as threatened under the ESA.

World Octopus Fisheries - Warwick H. H. Sauer; Ian G. Gleadall; Nicola Downey-Breedt; Zöe Doubleday; Graham Gillespie; Manuel Haimovici; Christian M. Ibáñez; Oleg N. Katugin; Stephen Leporati; Marek R. Lipinski; Unai Markaida; Jorge E. Ramos; et al. (Reviews in Fisheries Science & Aquaculture, 2021)

Laboratory Investigation of Liquid Injectivity in Surfactant-Alternating-Gas Foam Enhanced Oil Recovery - J. Gong; S. Vincent-Bonnieu; R. Z. Kamarul Bahrim; C. A. N. B. Che Mamat; J. Groenenboom; R. Farajzadeh; W. R. Rossen (Transport in Porous Media, 2020)

The joint impact of smoking plus alcohol drinking on treatment of pulmonary tuberculosis - Y. Ma; N.-Y. Che; Y.-H. Liu; W. Shu; J. Du; S.-H. Xie; Liang Li (European Journal of Clinical Microbiology & Infectious Diseases, 2019)

Out‐of‐Tibet: the spatio‐temporal evolution of Gentiana (Gentianaceae) - Adrien Favre; Ingo Michalak; Chih‐Hsiung Chen; Jenn‐Che Wang; James S. Pringle; Sabine Matuszak; Hang Sun; Yong‐Ming Yuan; Lena Struwe; Alexandra N. Muellner‐Riehl (Journal of Biogeography, 2016)
Aim We investigated the historical biogeography and diversification of Gentiana L. (Gentianaceae). Our study depicts the origin and dispersal routes of this alpine genus, and the role of the uplift of the Qinghai–Tibet Plateau ( QTP ) and past climate changes as triggers for its diversification. Location Tibeto‐Himalayan region and world‐wide mountain habitats. Methods Our sampling represents more than 50% of the extant Gentiana species, including all sections across their entire geographical ranges. We investigated the evolutionary history of Gentiana using phylogenetic reconstructions (maximum likelihood and Bayesian inference) of ITS , atp B– rbc L and trn L– trn F sequences, as well as molecular dating with beast . We tested two approaches of ancestral area reconstructions ( DEC , DIVA ) in BioGeo BEARS and investigated diversification rates using BAMM . Results The common ancestor of Gentiana and subtribe Gentianinae lived in the QTP region at around 34 (25–45) million years ago (Ma), and 40 (29–52) Ma respectively. From the surroundings of the QTP , Gentiana lineages dispersed to eastern China, Taiwan, Europe, North and South America, Australia and New Guinea, from mid‐Miocene onward ( c . 15 Ma–present), with only one older dispersal event to Europe ( c . 37–21 Ma). Diversification rates gradually increased over time, and two switches of diversification rates were identified in Gentianinae ( c . 7 Ma, simultaneously in the Pneumonanthe / Cruciata lineage and in Tripterospermum ). Main conclusions Gentiana existed in the QTP region throughout most of its uplift history following the India‐Asia collision. This region acted as the primary source area for dispersals to many areas of the world. Because steady increase in diversification rates coincides with the extension of the QTP , we argue that the museum theory rather than the explosive radiation theory prevails for gentians in this region, although rare shifts of diversification rates are associated with niche shifts across the alpine/subalpine ecotone.

The Bifunctional Liposomes Constructed by Poly(2-ethyl-oxazoline)-cholesteryl Methyl Carbonate: an Effectual Approach to Enhance Liposomal Circulation Time, pH-Sensitivity and Endosomal Escape - Huan Xu; Wei Zhang; Yan Li; Fei F. Ye; Peng P. Yin; Xiu Yu; Mei N. Hu; Yuan S. Fu; Che Wang; De J. Shang (Pharmaceutical Research, 2014)

The (TTTA) n polymorphism in intron 4 of CYP19 and the polycystic ovary syndrome risk in a Chinese population - P. Xu; X. L. Zhang; G. B. Xie; C. W. Zhang; S. M. Shen; X. X. Zhang; Y. X. Cao; W. J. Wang; Y. N. Che; Y. J. Xia; X. K. Wu; L. Yi; et al. (Molecular Biology Reports, 2013)

B MEY as a fisheries management target - Quentin R Grafton; Tom Kompas; Tuong N Che; Long Chu; Ray Hilborn (Fish and Fisheries, 2012)
This paper evaluates the implications of managing fisheries to achieve a B MEY target, or a biomass level that maximizes net economic returns in the fishery, and discusses the role of private ownership and the trade‐offs between economic and conservation benefits in this setting. The paper shows how a B MEY target can be used to: (i) determine relative employment and profitability measures; (ii) account for both the harvesting and processing sectors; and (iii) incorporate the interests of consumers and producers of fish. The profits–employment trade‐off of adopting a B MEY target vs. a traditional B MSY target is calculated using a model and data from the Western and Central Pacific tuna fisheries (WCPTF), while a generic bioeconomic model is constructed to show numerical values of B MEY from including processing and/or retail sectors and the consumer benefits of harvesting fish. For the WCPTF, results show that the long‐term gains per job lost from pursuing a B MEY target are worth several times the value of the average GDP per capita of Pacific Island Countries. The generic bioeconomic model shows that including a processing and/or retail sector, as well as measures of consumer benefit, lowers the B MEY target. However, there remains a broad range of parameter values for which B MEY is still greater than biomass at maximum sustainable yield, or B MSY . The paper also illustrates cases where B MEY > B MSY at different values of the price elasticity of demand, margins for processing and/or retail sectors and values of the discount rate.

The Role of Intermolecular Interactions in Solid State Fluorescent Conjugated Polymer Chemosensors - Sherryllene S. Pinnock; Catherine N. Malele; Justin Che; Wayne E. Jones (Journal of Fluorescence, 2012)

Chronic treatment with monoamine oxidase-B inhibitors decreases cocaine reward in mice - Ming-Che Ho; Chianfang G. Cherng; Yen-Ping N. Tsai; Chih-Yuan Chiang; Jia-Ying Chuang; Shu-Fang Kao; Lung Yu (Psychopharmacology, 2009)

Typing keystroke duration changed after submaximal isometric finger exercises - Che-Hsu (Joe) Chang; Peter W. Johnson; Jeffrey N. Katz; Ellen A. Eisen; Jack T. Dennerlein (European Journal of Applied Physiology, 2009)

Smoke plume detection in the eastern United States using MODIS - Y. Xie; J. J. Qu; X. Xiong; X. Hao; N. Che; W. Sommers (International Journal of Remote Sensing, 2007)